PREVENTION OF BRIBERY IN THE PRIVATE SECTOR IN INDONESIA ACCORDING TO THE UNITED NATIONS CONVENTION AGAINST CORRUPTION - Indra Kurniawan (NOMOI Law Review, 2021)
Acts of corruption in the private sector regulated within UNCAC include illicit enrichment, embezzlement of wealth in the private sector, bribery in the private sector, and trade in influence. The focus of the problem in this study is how to prevent and eradicate bribery in the private sector as a crime of corruption in Indonesia according to the United Nations Convention Against Corruption (UNCAC). Based on the results of the study it is understood bribery as part of the fraud is a crime that often occurs in organizations both government and private parties in certain activities. Fraud in the form of bribes is caused by several elements, among others; Pressure pressure is an encouragement to commit fraud (Fraud) on employees (employee Fraud) and by managers (management Fraud) and encouragement, Opportunity. There needs to be an understanding from law enforcement officials that the use of private sector bribery in Indonesia is an act of bribery as stipulated in the Law on Bribery Where the Law can be used to ensnare bribery perpetrators in the private sector.Keywords: Prevention and Eradication of Bribery, Private Sector, United Nations Convention Against Corruption (UNCAC).